2018
DOI: 10.1111/jace.15569
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to prepare self‐lubricity of Si3N4/Ag composite: Microstructure, mechanical and tribological properties

Abstract: Si3N4/Ag composites were firstly prepared through SPS technology, using Si3N4 and AgNO3 as raw materials. Utilizing the coordination bonding of Ag+ ions with nitrogen atoms of Si3N4, in situ generated Ag particles about 1 μm were tightly anchored on Si3N4 surface, thereby preventing the outflow of silver during sintering process. Meanwhile, smaller silver particles about 20 nm were located at the grain boundaries of Si3N4, which effectively improved the mechanical and tribological properties of Si3N4‐based com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It has been reported that the additions of silver oxide (Ag 2 O) in ceramics yield the Ag particle size around 1-2 μm. 36,37 The decomposition of AgNO 3 during SPS process enables to precipitate smaller particle sizes.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the additions of silver oxide (Ag 2 O) in ceramics yield the Ag particle size around 1-2 μm. 36,37 The decomposition of AgNO 3 during SPS process enables to precipitate smaller particle sizes.…”
Section: Microstructurementioning
confidence: 99%
“…These effects cause the glass to become ductile, which contributes to the improvement in the fracture toughness. Ag microparticles have been reported to toughen ceramics such as Al 2 O 3 , Si 3 N 4 , and HAp composites, [36][37][38]45,46 but these reported increments in fracture toughness are below 60% for ceramics despite addition of much larger amounts of Ag (10 vol%). Sub-micron Ag in SiO 2 glass fabricated in this work was much more effective compared to these reports.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Among metallic nanoparticles, Ag-base nanoparticles have received particular attention owing to their stable chemical characteristic, soft quality and high ductility, indicating an effective lubricating material (Si et al , 2018; Akgul and Simsir, 2021). Micro/nanosilver particles not only have excellent physical properties of silver but also unique scale properties of nanomaterials, which has a broad application in industrial lubrication fields (Si et al , 2018; Xu et al , 2018; Liu et al , 2018; Akgul and Simsir, 2021). Some recent studies have already shown promising results for silver additives at low to moderate temperatures (Sadri and Ashrafizadeh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 For example, K 4 TiO 4 whiskers have excellent infrared reflection ability, which can keep the surface temperature of friction materials low, conducive to the stability of friction coefficient and improvement of wear resistance. Si 3 N 4 whiskers can increase the composite's hardness, thereby improving its friction performance [6][7][8] . Studies of Hu et al 9 have shown that K 4 TiO 4 whiskers can improve the wear resistance and significantly reduce the wear rate of polymer-based composites.…”
Section: Introductionmentioning
confidence: 99%